Detailed Mechanism of the Reaction of Phenylboronic Acid Derivatives with D‐Fructose in Aqueous Solution: A Comprehensive Kinetic Study. Issue 16 (10th October 2016) - Suzuki, Yota; Shimizu, Mika; Okamoto, Takuya; Sugaya, Tomoaki; Iwatsuki, Satoshi; Inamo, Masahiko; Takagi, Hideo D.; Odani, Akira; Ishihara, Koji
Abstract: A detailed kinetic study of the reactions of phenylboronic acid (PhB(OH)2 ), 2‐methylphenylboronic acid (2‐MePhB(OH)2 ), 2‐isopropylphenylboronic acid (2‐ i PrPhB(OH)2 ), and 1‐hydroxy‐3H‐2, 1‐benzoxaborole (BxB(OH)) with D‐fructose was carried out to clarify the nature of the reactive boron species in D‐fructose sensing and investigate the corresponding reaction mechanism. Both the boronic acids (RB(OH)2 ) and boronate ions (RB(OH)3 − ) were reactive toward D‐fructose, while out of the five D‐fructose anomers only α‐D‐fructofuranose was reactive toward boron species. The reactions of all substrates proceeded consecutively in two steps (steps 1 and 2). We concluded that the first intermolecular step (step 1) corresponds to the parallel reactions (two parallel reactions for 2‐ i PrPhB(OH)2 and three for the other systems) of the boronic acid and the boronate ion with α‐D‐fructofuranose to form bicoordinate complexes (mixture of exo‐ and endo‐isomers), and the second intramolecular step (step 2) corresponds to the formation of a tricoordinate α‐D‐fructofuranose complex from the bicoordinate complexes. It was found that both the boronic acid and the boronate ion were kinetically reactive toward D‐fructose, with the latter being more reactive. Abstract : Reactions of boronic acids RB(OH)2 (R=phenyl, 2‐methylphenyl, and 2‐isopropylphenyl) and BxB(OH) (1‐hydroxy‐3H‐2, 1‐benzoxaborole) with D‐fructose in alkaline solution involve the following reactive species: RB(OH)2, RB(OH)3 −, BxB(OH), BxB(OH)2 −, and β‐D‐fructofuranose. The reaction proceeds in two consecutive steps: the intermolecular formation of a bicoordinate fructofuranose complex is followed by the intramolecular formation of the tricoordinate fructofuranose complex.